Women Navigating Their Feelings Towards Finland; Interviews with Arabs Seeking Asylum - Ibrahim, Yasmin (My University, 2019)
Finland is a country in Northern Europe which has popularized tolerance towards minorities and asylum seekers since it gained independence from Russia 101 years ago. While much research has been done about the experiences of immigrants and minorities in Finland, the feelings of asylum seekers in Finland has not been researched extensively. In effort to center them and understand how their feelings towards Finland are navigated, two interviews were conducted with Arabic women seeking asylum in Finland. Sara Ahmed’s understanding of feelings lead the analysis on the three themes of exhaustion, islamophobia and femonationalism in this re-search. Through looking at feelings in the analysis of these three themes, I found that my informants do not have control over how they navigate their feelings towards Finland, and through this conclusion, more research and encouragement of the discussion of bad feelings with the asylum seeking community in Finland is hypothesized to yield more representative and humanistic understanding of the struggles of seeking asylum in Finland.
Keywords: asylum seekers, Finland, feelings, Arabic women, Islamophobia, exhaustion, Femonationalism.